Lucretia Davidson in Europe: Female Elegy, Literary Transmission and the Figure of the Romantic Poetess - Vincent, Patrick (Romanticism on the Net, 2003)
AbstractThis essay heeds Yopie Prins’s recent call to abandon critical attempts to recover the subjectivity of (real) poetesses and instead to look at the culturally constructed figure of the “poetess.” It describes the early reception history of American poetess Lucretia Davidson who died at 16, (possibly of anorexia nervosa). Focused as it was on her death, this transatlantic body of criticism (Southey, Poe) and tribute (Desbordes-Valmore, Karolina Pavlova) offers to the poetess tradition a women’s ethic of self-sacrifice enabling a female form of literary transmission that celebrates women’s interchangeability rather than their uniqueness. An elegy by French poetess Marceline Desbordes-Valmore manipulates Davidson’s image as a means of insisting on the abstemiousness (to the point of death) of the poetess figure despite her hyperproductivity, and then ultimately insists upon the interchangeability and solidarity of women poets. In contrast, Karolina Pavlova’s elegy to Davidson carves out of this transmissible figure her own particular identity, leading to the masculinization of Pavlova’s poetry by Russian critics – and, unfortunately, to Pavlova’s subsequent obscurity. This essay leaves open the question as to which of these two elegists made the “better” choice, delineating instead options for transcontinental women poets in shaping their own subsequent transmission.